2012
DOI: 10.1039/c2sm00032f
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray propagation imaging of a lipid bilayer in solution

Abstract: We have used X-ray propagation imaging to visualize a less than 5 nm thick native lipid bilayer membrane freely suspended in aqueous solution. Contrast is formed by free space propagation of hard X-rays, with the membrane illuminated by a nano-focused, partially coherent synchrotron beam, at a controllable distance (defocus) behind the focal spot. Quantitative fitting of the magnified Fresnel fringes shows the transition from membranes swollen with solvent to the native bilayer, containing structural informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…We dissolved Nile red in the decane to check for the presence of remaining organic solvent enclosed between the two leaflets of the membrane bilayer (Figure 2d). Except for the area in close vicinity of the well edge (Plateau–Gibbs border),39 in which the two leaflets do not associate due to an enclosed solvent annulus,40 the Nile red fluorescence signal was negligible, which indicates that the two leaflets form a tight lipid bilayer in the center area of the wells. In some cases we actually observed the process of bilayer formation and the associated “zipping” of the two membrane leaflets in real time.…”
Section: Resultsmentioning
confidence: 99%
“…We dissolved Nile red in the decane to check for the presence of remaining organic solvent enclosed between the two leaflets of the membrane bilayer (Figure 2d). Except for the area in close vicinity of the well edge (Plateau–Gibbs border),39 in which the two leaflets do not associate due to an enclosed solvent annulus,40 the Nile red fluorescence signal was negligible, which indicates that the two leaflets form a tight lipid bilayer in the center area of the wells. In some cases we actually observed the process of bilayer formation and the associated “zipping” of the two membrane leaflets in real time.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, bilayer stability is linked to annulus stability, which in turn relates to favorable contact angles of the solvent with the aperture material (14). Indeed, Beerlink et al (15) recently obtained a cross-sectional view of the decane annulus of a suspended bilayer in a kapton (polyimide) channel by x-ray propagation imaging, which visualizes how the annulus connects the bilayer to the solid material by wetting tens of micrometers of the kapton channel wall. We speculate that the shaped apertures stabilize the bilayer by providing an anchor region for the annulus, with the shape and hydrophobicity of the tapered regions preventing excessive drainage or lateral movement of the solvent annulus.…”
Section: Discussionmentioning
confidence: 99%
“…The aperture-suspended bilayer is formed by the Mueller-Rudin (painting) method, in which an oil-lipid solution is deposited on the aperture and the bilayer forms when the oil phase has thinned to a sufficient extent (9), or by the Montal-Mueller (folding) method (10), in which an air-water interface with a lipid monolayer is raised over both sides of the aperture, which is typically pretreated with an apolar solvent (11,12). Although the folding method involves a substantially smaller amount of solvent than the painting method, both protocols result in a planar bilayer that is connected to the wall of the aperture by a solvent annulus, which is also referred to as the Plateau Gibbs border (6,(12)(13)(14)(15). The septum material should be sufficiently hydrophobic to enable draining of excess solvent, have suitable electrical properties (high resistivity, low dielectric constant, and low dielectric loss), be mechanically strong, and chemically compatible with cleaning solutions (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The additional micro-tapered structure would be expected to improve tolerance to mechanical stimuli which might distort the shape of the BLMs on a micrometer-scale. For example, it has been reported that BLMs easily form bulges upon application of stimuli, such as osmotic pressure, an applied force and hydrostatic pressure 41 43 . If the present BLMs also bulged to a similar extent as phosphocholine BLMs in an aperture (ϕ~1 mm) 44 , the bulging depth was estimated to be ~3.5 μm for the BLMs in the present aperture (ϕ~25 μm).…”
Section: Discussionmentioning
confidence: 99%